Analisis Cacat Casting Akibat Variasi Lama Waktu Pengerasan dan Persentase Binder di PT. Barata Indonesia - Ramadhanu, Arya; Syuhri, Ahmad; Djumhariyanto, Dwi (ROTOR, 2014)
Sand inclusion and pin hole are surface defects caused by molding sand. Therefore need by varying age sand and percentage of binder in sand molds. The purpose of this research to improve the quality of the product. Each treatment will through tensile strength test, then make a plate pattern for casted . Each plate will checked defects that occur, sand inclusion and pin hole . Data from this research will be analyzed using ANOVA factorial design 2x3. The results of this research with a percentage of 1.5% binder and age sand 24 hour produce sand inclusion of 0% and pin hole, 2 holes. Keywords: Sand inclusion, pin hole, binder, age sand